Highly Active and Reusable Kenaf Cellulose Supported Bio-Poly(hydroxamic acid) Functionalized Copper Catalysts for C–N Bond Formation Reactions - Siti Hajar Mohamad Ros (BioResources, 2016)
Distinctly active poly(hydroxamic acid) anchored copper (Cu) catalysts were synthesized from chemically modified kenaf cellulose. They were characterized by Fourier transform infrared spectroscopy (FT-IR), field emission scanning microscopy (FESEM), high resolution transmission electron microscopy (HRTEM), inductively coupled plasma atomic emission spectrometry (ICP-AES), UV-vis spectroscopy (UV), and X-ray photoelectron spectroscopy (XPS). The Cu-catalysts were successfully applied to the Michael addition reaction of amines with α,β-unsaturated carbonyl/cyano compounds and to the Click reactions of organoazides with alkynes under mild reaction conditions. The catalysts enabled excellent yields (88% to 95%) in both of the C–N bond formation reactions and showed easy recycling with outstanding reusability for seven cycles without any distinguished decrease in their catalytic activity.